Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1080/15592294.2017.1325065
|View full text |Cite
|
Sign up to set email alerts
|

Maternal cigarette smoking during pregnancy and offspring DNA methylation in midlife

Abstract: Maternal smoking in pregnancy (MSP) has been associated with DNA methylation in specific CpG sites (CpGs) in infants and children. We investigated whether MSP, independent of own personal active smoking, was associated with midlife DNA methylation in CpGs that were previously identified in studies of MSP-DNA methylation in children. We used data on MSP collected from pregnant mothers of 89 adult women born in 1959-1964 and measured DNA methylation in blood (granulocytes) collected in 2001-2007 (mean age: 43 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 38 publications
7
51
0
1
Order By: Relevance
“…Findings are also consistent with a recent report that highlighted persistence of DNA methylation levels related to prenatal smoke exposure into adulthood, 17 which identified associations the same CpG sites located in MYO1G and CYP1A1 , and other CpG sites in FTO and AHRR .…”
Section: Discussionsupporting
confidence: 92%
“…Findings are also consistent with a recent report that highlighted persistence of DNA methylation levels related to prenatal smoke exposure into adulthood, 17 which identified associations the same CpG sites located in MYO1G and CYP1A1 , and other CpG sites in FTO and AHRR .…”
Section: Discussionsupporting
confidence: 92%
“…The longitudinal analysis showed that differentially methylated CpGs observed around age 30 persisted into middle age (around age 48) without significant change in direction or magnitude of methylation levels. This corroborates the findings of recent smaller studies, which found several differently methylated CpGs in middle-aged women exposed to maternal smoking in utero 14,15 and suggests that some of the prenatal smoking exposure associated methylation changes are largely irreversible and unaffected by age and/or environmental exposures later in life. To assess whether such persistent changes in DNA methylation are causally implicated with disease, we performed a Mendelian randomization analysis using summary data from large epigenome-wide association studies 24 .…”
Section: Discussionsupporting
confidence: 90%
“…In support of this, an epigenome-wide meta-analysis of 13 birth cohort studies identified over 6,000 differentially methylated CpGs in cord blood of newborns exposed to prenatal smoking 11 . Several smaller studies have suggested that some of these methylation changes may persist across childhood and adolescence 12,13 into adulthood 14,15 . However, questions remain concerning whether such DNA methylation changes endure across the life course and whether they play a mediating role in linking prenatal smoke exposure to later life health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, in this study, we identified six novel sites, which were replicated across tissues, using the 850k newer chip design. Several well-documented findings were replicated in this study, including DNAm of the AHRR gene on chromosome 5, which has previously been associated with both adult and maternal smoking [14][15][16][17]. The aryl-hydrocarbon receptor (AhR) pathway and the methylation of the related AHRR gene has been proposed as a potential biomarker of cardiovascular disease, specifically atherosclerosis, in smokers [9].…”
Section: Discussionsupporting
confidence: 67%